Multimedia Tools to Learn About Nanoparticles Characterization - Santos, Tiago José Miranda (2013)
This work presents the production of multimedia tools for distance learning about nanoparticles characterization. The module is fundamentally based on hypermedia contents and can be included in a course delivered in an e- or b-learning format. Hypermedia can include several interactive multimedia contents such as interactive video, hypertext, photos, audio, animations or computer graphics, which can be combined among them. In this work the objective was to develop an interactive video to explain the nanoparticles characterization using dynamic light scattering. This option allows the user to choose the better strategy to learn about the measuring technique, since the video is prepared for interaction and offers the access to complementary information using different hypermedia contents. These aspects are particularly important for lifelong learning courses, dedicated to users already in the job market, for whom the access to real laboratories can be more difficult and restricted